Implementing knowledge into practice for improved neonatal survival; a cluster-randomised, community-based trial in Quang Ninh province, Vietnam - Huy Tran Q; Hoa Dinh P; Persson Lars-Åke; Eriksson Leif; Nga Nguyen T; Målqvist Mats; Wallin Lars; Duc Duong M; Ewald Uwe (BMC, 2011)
Abstract Background Globally, almost 4 million newborns die during the first 4 weeks of life every year. By increased use of evidence-based knowledge in the healthcare system a large proportion of these neonatal deaths could be prevented. But there is a severe lack of knowledge on effective methods for successful implementation of evidence into practice, particularly in low- and middle-income countries. Recent studies have demonstrated promising results with increased survival among both mothers and newborns using community-based approaches. In Vietnam evidence-based guidelines on reproductive health were launched in 2003 and revised in 2009. The overall objective of the current project is to evaluate if a facilitation intervention on the community level, with a problem-solving approach involving local representatives if the healthcare system and the community, results in improvements of neonatal health and survival. Methods/Design The study, which has been given the acronym NeoKIP (Neonatal Health - Knowledge Into Practice), took place in 8 districts composed by 90 communes in a province in northern Vietnam, where neonatal mortality rate was 24/1000 in 2005. A cluster randomised design was used, allocating clusters, as defined as a commune and its correponding Commune Health Center (CHC) to either intervention or control arm. The facilitation intervention targeted staff at healthcare centres and key persons in the communes. The facilitator role was performed by lay women (Women's Union representatives) using quality improvement techniques to initiate and sustain improvement processes targeting identified problem areas. The intervention has been running over 3 years and data were collected on the facilitation process, healthcare staff knowledge in neonatal care and their behaviour in clinical practice, and reproductive and perinatal health indicators. Primary outcome is neonatal mortality. Discussion The intervention is participatory and dynamic, focused on developing a learning process and a problem-solving cycle. The study recognises the vital role of the local community as actors in improving their own and their newborns' health, and applies a bottom-up approach where change will be accomplished by an increasing awareness at and demand from grass root level. By utilising the existing healthcare structure this intervention may, if proven successful, be well suited for scaling up. Trial registration Current Controlled Trials ISRCTN44599712